PENANAMAN NILAI-NILAI ISLAM DAN PATRIOTISME KEPADA MASYARAKAT MELALUI PERINGATAN HUT RI KE-80 DI DESA CAMPUREJO - Risni, Titin Widya; Hendy; Vitasmoro, Pamadya; Khotimah, Adinda Khusnul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This community service activity aims to instill and strengthen Islamic values ​​that align with the spirit of patriotism in the lives of the people of Campurejo Village, especially in commemoration of the 80th Anniversary of the Republic of Indonesia. The people of Campurejo Village are known as a religious community with a strong national spirit. Therefore, the integration of Islamic and national values ​​is seen as crucial as an effort to strengthen national identity, build moral character, and maintain social unity and harmony at the village level. The implementation of this activity is designed in various forms of educational and participatory activities, including thematic group discussions, competitions that highlight Islamic and national values, and an evening of reflection on independence. The series of events aims to raise collective awareness of the community regarding the importance of practicing Islamic teachings in daily life while fostering a sense of love for the homeland. The methods used include a participatory approach that actively involves the community, interactive lectures that encourage two-way dialogue, and values-based education that is contextualized to the lives of the village community. The results of this community service activity demonstrate an increased understanding of Islamic values, such as honesty, mutual assistance, responsibility, and social awareness. Furthermore, the community has grown to understand the importance of patriotism, such as love for the homeland, appreciation for the services of heroes, and a commitment to maintaining national unity. It is hoped that this activity can serve as a model for sustainable values ​​education and strengthen social cohesion and national character within the village community.